Innovation of Silicon Fertilizer Based on Agricultural Waste to Address Fertilizer Scarcity in the Harapan Jaya Farmer Group, Pamekasan - Sundahri, Sundahri; Saleh, Azmi; Harsanti, Restiani Sih; Fariroh, Indri; Munandar, Denna Eriani; Musyaffa', Hudzaifah; Pramudya, Frisco Sendy; Suwono, Hadi; Wati, Henny Diana; Maulidi, Fathoni Ilham; Maharani, Aulia Febrina (Pascasarjana Universitas Mataram, 2025)
The relatively high price of inorganic fertilizers means that members of the Harapan Jaya Farmer Group are unable to optimally meet their fertilizer needs. On the other hand, farmers have not been able to process their agricultural waste properly which is generally only by burning. This method is not environmentally friendly because it can pollute the air, lose its nitrogen content and kill soil organisms that are useful for plants. In fact, there is no return of crop residues to the land. This condition can cause soil fertility to decrease and requiring more fertilizer inputs. This additional input has an impact on increasing the cost of farming. To solve above problems, this community service program had been undertaken in April to November 2024 through counseling, training and mentoring to farmers who are members of the farmer group as the partner in this program. The focus of this program was mainly on the management of gramine crop waste such as rice and corn which absorb very high silicon element. The results of this service showed that the training participants were very enthusiastic in attending the counselling and could absorb the presented materials. Almost all participants were able to overcome the techniques or methods in the process of making silicon fertilizer during the training. In addition, they were also very interested in trying the fermented and well-designed fertilizer based on the respondent’s assessment. However, applying fertilizer in the form of demo plots requires separate planning in the future because the process of making silicon fertilizer takes very long time.